2016
DOI: 10.1007/s11517-016-1544-3
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the mean strength and variations of the time-to-time fluctuations of resting-state brain activity

Abstract: The time-to-time fluctuations (TTFs) of resting-state brain activity as captured by resting-state fMRI (rsfMRI) have been repeatedly shown to be informative of functional brain structures and disease-related alterations. TTFs can be characterized by the mean and the range of successive difference. The former can be measured with the mean squared successive difference (MSSD), which is mathematically similar to standard deviation; the latter can be calculated by the variability of the successive difference (VSD)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…Percent amplitude of fluctuation of normalized mean squared successive difference and variability of the successive difference between the EO-EC sessions [41]. EO and EC difference was associated with spontaneous BOLD oscillations in cortical sensory [42].…”
Section: Between-condition Differences With and Without Standardizatimentioning
confidence: 89%
“…Percent amplitude of fluctuation of normalized mean squared successive difference and variability of the successive difference between the EO-EC sessions [41]. EO and EC difference was associated with spontaneous BOLD oscillations in cortical sensory [42].…”
Section: Between-condition Differences With and Without Standardizatimentioning
confidence: 89%
“…Temporal variability can be calculated in many forms, such as variance (He, 2011 ), standard deviation (SD) (Garrett et al, 2013a ), mean square successive difference (MSSD) (Samanez-Larkin et al, 2010 ; Li et al, 2017 ). Here in this study, the temporal variability of isEEG was quantified by the normalized mean squared successive difference (nMSSD) (Neumann et al, 1941 ).…”
Section: Methodsmentioning
confidence: 99%
“…Mean squared successive difference (MSSD) is a popularly used metric to characterize the temporal variability of physiological signals such as heart rate and fMRI BOLD signals (Berntson et al, 2005 ; Samanez-Larkin et al, 2010 ). Compared with other measures of temporal variability (such as SD), MSSD is not affected by low frequency drift and thus is more robust and reliable (Neumann et al, 1941 ; Li et al, 2017 ). Furthermore, because of the inherent relationship between signal strength and signal variability (i.e., the temporal variability calculated as MSSD or SD is positively correlated with the magnitude), MSSD should be normalized by RMS to disassociate the influence of signal strength (i.e., the magnitude) from signal variability.…”
Section: Methodsmentioning
confidence: 99%
“…Studies have demonstrated that there are widespread significant differences in spontaneous brain activity between eyes-open (EO) and eyes-closed (EC) resting states using the functional magnetic resonance imaging (fMRI) technique. From the regional activity aspect of spontaneous brain activity, it was found that regional activity in the EO resting state was significantly higher in the bilateral middle occipital gyrus (MOG), orbital frontal cortex, right cuneus, fronto-parietal cortex and cerebellum regions, but significantly lower in the sensorimotor, visual, auditory, right paracentral lobule (PCL), retrosplenial cortex, insula, thalamus and cingulo-opercular regions compared to that in the EC resting state, by using the amplitude of low frequency fluctuation (ALFF; Yang et al, 2007 ; Yan et al, 2009 ; Liu et al, 2013 ; Zou et al, 2015 ; Qin et al, 2018 ), spectral density of the blood oxygenation level dependent signal (McAvoy et al, 2008 , 2012 ), amplitude of spontaneous activity (Bianciardi et al, 2009 ; Zou et al, 2015 ), fractional ALFF (fALFF; Jao et al, 2013 ; Liang et al, 2014 ; Li Z. et al, 2016 ), and regional homogeneity (ReHo; Liu et al, 2013 ; Song et al, 2015 ) measures. From the regions synchronization aspect of spontaneous brain activity, it was found that functional connectivity in the EO resting state was significantly greater between the posterior cingulate cortex (PCC) and other brain areas, but significantly smaller between the whole thalamus and visual cortex, the PCC and the bilateral perisylvian regions, as compared to the EC resting state (Yan et al, 2009 ; Zou et al, 2009 ; Jao et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%